Zika Virus Infection and Guillain–Barré Syndrome in Three Patients from Suriname - Langerak, Thomas; Yang, Harvey; Baptista, Mark; Doornekamp, Laura; Kerkman, Tessa; Codrington, John; Roosblad, Jimmy; Vreden, Stephen G. S.; De Bruin, Erwin; Mögling, Ramona; Jacobs, Bart C.; Pas, Suzan D.; et al. (Frontiers in Neurology, 2016)
We present three patients from Suriname who were diagnosed with Guillain-Barré syndrome (GBS) during the Zika virus (ZIKV) outbreak in this country. One patient had a positive ZIKV urine real-time RT-PCR (qRT-PCR) result. The other two patients had a negative ZIKV urine qRT-PCR but a positive virus neutralisation test and presence of IgG antibodies against ZIKV in the serum. Considering the evidence of a past ZIKV infection and absence of evidence for recent infections with the most common preceding infections of GBS, it is very likely that these GBS cases were triggered by ZIKV.